PERANAN PENJADWALAN OPERASI TERHADAP PENINGKATAN EFESIENSI PADA PEMBANGUNAN JEMBATAN RUMPIANG DI PT VIRAMA KARYA - Dewi Taurusyanti; Mico Afriansyah (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2013)
ABSTRACT Basically when built the company we all have a hope that the company will develop someday and get the target, such as maximum profit or make a product or service with the use of maximum resources. Schedulling is an allocation decision of resources made available by facilities decision an aggregate planning. Schedulling is an important part of activity in the company, because it refers to the process of preparing a time target for all production operating activities including set up and after preparation time in executing a production order. The research use descriptive explorative method by case study, and the type of the research technique is statistic quantitative using PERT-CPM method. The analysis unit of this research is the construction unit of the company. PERT CPM analysis allows uncertainty in the activity times when activity times are difficult to predict, PERT can provide estimates the impact of uncertainty on the projects completion time. However, reason given in the analysis results are only approximation, because there are other factors contibuted in bridge project. Analysis method with CPM, can useful for the company to know about the efficiency time and cost from operation schedulle. From the analysis result can be described that normal time is 320 weeks can be reduced to 224 weeks resulting in 70% of throughput efficiency. Key Words; Operations Management, Project Management, Operation Schedulling, CPM Method, Act of Determining Time and Raising Efficiency